Impact of Corona Treatment on Mechanical Properties and Morphology of Hemp Fiber Reinforced in Epoxy Matrix Composite - Patanapisalsin, Kittipong; Photiphitak, Chanu; Artnaseaw, Apichart (Journal of Research Updates in Polymer Science, 2025)
Corona treatment was applied to enhance the interfacial adhesion between hemp woven fibers and epoxy resin in fiber-reinforced composites. Using a cold pressing method with equal parts of resin and fiber (50 g each), samples were treated for 1–4 min. SEM analysis revealed that increased treatment time led to greater fiber surface roughness and reduced voids at the fiber–matrix interface, improving bonding. Tensile strength increased with treatment time, peaking at 48.68 MPa at 3 min before slightly decreasing at 4 min. The elastic modulus remained stable (304.67–312.52 MPa) up to 3 min, then dropped slightly to 302.86 MPa. Overall, corona-treated composites exhibited a 55% increase in tensile strength compared to untreated ones, confirming the treatment’s effectiveness in enhancing mechanical performance.